Microfluidics: IFlowPlate—A Customized 384‐Well Plate for the Culture of Perfusable Vascularized Colon Organoids (Adv. Mater. 46/2020). Issue 46 (17th November 2020) - Rajasekar, Shravanthi; Lin, Dawn S. Y.; Abdul, Lyan; Liu, Amy; Sotra, Alexander; Zhang, Feng; Zhang, Boyang
Abstract : Human stem‐cell‐derived organoids have provided new opportunities to model biological processes and recapitulate organ development. However, organoid systems lack perfusable vascular networks to deliver nutrients and drugs. In article number 2002974, Boyang Zhang and co‐workers introduce IFlowPlate—a microfluidic system with an "open‐well" design in a 384‐well plate format that can be used to vascularize and intravascularly perfuse organoids. This image shows three independently perfused microvascular networks in an IFlowPlate.